The Moderating Role of Intellectual Capital Between Enterprise Risk Management and Firm Performance: A Conceptual Review - Khan, Sajjad Nawaz; Ali, Engku Ismail Engku (American Journal of Social Sciences and Humanities, 2017)
Nowadays, businesses have focused more to develop effective risk management practices to enhance firm performance as managers and decision makers are considering holistic view of risk management despite of silo-based context. In recent years, many organizations have improved their performance by utilizing ERM framework to manage diversified range of risks because enterprise risk management (ERM) is considered as most admirable practice in this era. Therefore the current study will help to investigate the influence of ERM on the firm performance by the moderating role of intellectual capital in relationship between ERM and firm performance. As, the firms with higher intellectual capital could more likely withstand the effects of unanticipated changes in economies and markets. Nonetheless, in future, the proposed framework and research model will also be empirically validated in the context of emerging country such as Pakistan, which will definitely contributes by filling the gap in the literature by delivering a clear deliberation for ERM implementation to achieve firm performance.